If n = 0 ∑ ∞ ( 4 n 3 4 ) = 2 k then k = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First note that ( m n ) = 0 for m > n . Therefore n = 0 ∑ ∞ ( n 3 4 ) = n = 0 ∑ 8 ( n 3 4 ) By binomial theorem , we have:
( 1 + x ) 3 4 ( 1 + 1 ) 3 4 ( 1 + i ) 3 4 ( 1 − 1 ) 3 4 ( 1 − i ) 3 4 = ( 0 3 4 ) + ( 1 3 4 ) x + ( 2 3 4 ) x 2 + ( 3 3 4 ) x 3 + ( 4 3 4 ) x 4 + ⋯ + ( 3 2 3 4 ) x 3 2 + ( 3 3 3 4 ) x 3 3 + ( 3 4 3 4 ) x 3 4 = ( 0 3 4 ) + ( 1 3 4 ) + ( 2 3 4 ) + ( 3 3 4 ) + ( 4 3 4 ) + ⋯ + ( 3 2 3 4 ) + ( 3 3 3 4 ) + ( 3 4 3 4 ) = ( 0 3 4 ) + ( 1 3 4 ) i − ( 2 3 4 ) − ( 3 3 4 ) i + ( 4 3 4 ) + ⋯ + ( 3 2 3 4 ) + ( 3 3 3 4 ) i − ( 3 4 3 4 ) = ( 0 3 4 ) − ( 1 3 4 ) + ( 2 3 4 ) − ( 3 3 4 ) + ( 4 3 4 ) − ⋯ + ( 3 2 3 4 ) − ( 3 3 3 4 ) + ( 3 4 3 4 ) = ( 0 3 4 ) − ( 1 3 4 ) i − ( 2 3 4 ) + ( 3 3 4 ) i + ( 4 3 4 ) + ⋯ + ( 3 2 3 4 ) − ( 3 3 3 4 ) i − ( 3 4 3 4 )
⟹ ( 1 + 1 ) 3 4 + ( 1 + i ) 3 4 + ( 1 − 1 ) 3 4 + ( 1 − i ) 3 4 = 4 ( ( 0 3 4 ) + ( 4 3 4 ) + ( 8 3 4 ) + ⋯ + ( 3 2 3 4 ) )
⟹ n = 0 ∑ ∞ = 4 ( 1 + 1 ) 3 4 + ( 1 + i ) 3 4 + ( 1 − 1 ) 3 4 + ( 1 − i ) 3 4 = 4 2 3 4 + ( 2 i ) 1 7 + 0 + ( − 2 i ) 1 7 = 2 3 2
Therefore, k = 3 2 .
Typo in the final answer!
Log in to reply
Thanks, I wonder why I made the mistake.
Problem Loading...
Note Loading...
Set Loading...
This is NOT my answer, I found it on Quora here and found it interesting and quite Brilliant
Let S = n = 0 ∑ ∞ ( 4 n 3 4 )
Using the property ( r n ) = ( n − r n ) we have
2 S = n = 0 ∑ ∞ [ ( 4 n 3 4 ) + ( 4 n − r 3 4 ) ]
Notice that this sum is [ ( 0 3 4 ) + ( 3 4 3 4 ) ] + [ ( 4 3 4 ) + ( 3 0 3 4 ) ] + [ ( 8 3 4 ) + ( 2 6 3 4 ) ] + …
Notice that as n gets large, the terms are 0 . With a little bit of rearranging: 2 S = n = 0 ∑ ∞ [ ( 4 n 3 4 ) + ( 3 4 − 4 n 3 4 ) ] = n even ∑ ∞ ( n 3 4 )
Now, using Pascal's identity, ( r n ) = ( r − 1 n − 1 ) + ( r n − 1 ) , we have that
2 S = n even ∑ ∞ ( n 3 4 ) = r = 0 ∑ ∞ ( r 3 3 ) = 2 3 3 Thus, S = n = 0 ∑ ∞ ( 4 n 3 4 ) = 2 3 2